THE ROLE OF THE TEACHER AND PARENT IN LANGUAGE DEVELOPMENT: A FOCUS ON INFANT SCHOOL - SAMKANGE, Dr. Wellington (IJRDO- Journal of Educational Research, 2016)
One of the miracles of development in education is how children learn, acquire and developlanguage. The school, apart from imparting knowledge and skills, has to provide for languagedevelopment in learners. The paper examines the role of the teacher in languagedevelopment. Different theories in development which include maturationist theory, theenvironmentalist theory, constructivist theory and interactionist theory are also examined.The study makes use of the mixed methodology and the case study design. The study focusedon one primary school in Chegutu, Zimbabwe. The school was purposively selected. The sixclasses observed included two ECD classes, two grade one classes and two grade two classes.The six teachers in the selected classes automatically became respondents in the study. Thestudy observed that while the teachers had the relevant qualifications, it was necessary forgrade one and two teachers to have an understanding of ECD-A and ECD-B expectations.The study observed that teachers used a variety of approaches to promote languagedevelopment in learners. The different approaches were characterised by the environmentalisttheory which argues that the environment shapes learning. The study also noted that whileparents played an important role in language development, the extent of their involvement inschool work was influenced by their level of education and economic status. The studyconcluded that lack of resources, limited time, and the heterogeneous nature of languageswithin communities; create challenges on language development at school level. The studyrecommends a collective effort by schools, parents and communities for resourcemobilisation and provision in order to support the teaching and learning of languages inschools.